Virtual reality games in improving motor skills and physical activity in children with intellectual disabilities: a scoping review - Yovhandra Ockta; Tri Susanti Sirait; Iqbal Maulana; Pramudya Wisnu Priambodo; Rahman Rahman (Indonesian Journal Education, 2026)
Virtual Reality (VR) has emerged as a promising technological innovation in education and rehabilitation, particularly for supporting motor development and physical activity among children with intellectual disabilities. This study aims to map and synthesize existing empirical evidence on the effectiveness of VR-based interventions in improving motor skills and physical activity in this population. A scoping review was conducted following PRISMA guidelines by systematically searching ScienceDirect, ProQuest, and Google Scholar databases for articles published between 2019 and 2025. From an initial yield of 1,009 studies, eight articles met the predefined inclusion criteria and were included in the final analysis. The findings indicate that VR-based interventions, especially those integrating virtual and real-world games, consistently improve walking ability, object control, and gross motor skills. Several studies also reported gains in muscle strength and coordination, although evidence regarding balance improvement remains inconsistent. Despite its potential benefits, challenges related to accessibility, intervention design, and individual adaptability persist. Overall, VR represents a valuable and engaging tool for enhancing motor skills and physical activity in children with intellectual disabilities. Future research should emphasize targeted program development, long-term outcome evaluation, and interdisciplinary collaboration to optimize VR-based rehabilitation and educational interventions.